Integrating Social-Emotional Learning in English Language Teaching: Teachers’ Perspectives, Pedagogical Practices, and Challenges - Makhroji; Evi Zulida; Muhammad Arif Sanjaya; Rahmiati (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to explore how Social-Emotional Learning is integrated into English Language Teaching by examining teachers’ perspectives, pedagogical practices, and implementation challenges, and to provide pedagogical implications for enhancing ELT practices, focusing on the Indonesian context of Kota Langsa, Aceh. Using a mixed-methods design, the research employed 50 questionnaires containing 30 items to gather quantitative data and conducted 12 in-depth interviews to collect qualitative insights. The study involved 50 English teachers from junior and senior high schools in Kota Langsa, Indonesia, representing public, private, and Islamic boarding schools. Quantitative data were analyzed using descriptive and inferential statistics, including independent-samples t-tests, with SPSS. Qualitative data were examined through thematic analysis. Integration of both strands enabled triangulation, generating findings that were both statistically grounded and contextually rich. Results indicated that while teachers demonstrated high awareness of SEL benefits (M = 4.32, SD = 0.45), their classroom practice remained moderate (M = 3.65, SD = 0.52), revealing a significant awareness-practice gap. Institutional constraints, limited training, and cultural issues were identified as major barriers, with public school teachers reporting more systemic challenges than private school teachers (p = 0.003, Cohen’s d = 0.88). Qualitative findings highlighted culturally responsive practices, such as integrating Islamic narratives, alongside the need for institutional support. The study concludes by recommending localized strategies and systematic training to bridge the gap between SEL awareness and classroom implementation.